Editorial: only steps away from primetime? Hepatitis B virus RNA as a routine marker to guide HBV treatment decisions—authors' reply. Issue 7 (10th September 2021) - Xia, Muye; Chi, Heng; Janssen, Harry L. A.; Peng, Jie
LINKED CONTENT: This article is linked to Xia et al and Wehmeyer & Schulze zur Wiesch papers. To view these articles, visit https://doi.org/10.1111/apt.16538 and https://doi.org/10.1111/apt.16560